The impact of social support on students' mental health: A new perspective based on fine art majors - Wei, Pengju (Frontiers in Psychology, 2022)
College students face a variety of challenges today, and the degree of their psychological health directly impacts their ability to overcome these challenges. A good psychological state helps college students to invest better in their career development and improve the degree of social integration. This paper uses the SCL-90 Symptom Self-Assessment Scale and the Social Support Rating Scale (SSRS) to investigate the mental health, psychological support, and social support of students from low income backgrounds in two universities in Hainan City. The research results showed that there was no significant difference between the objective support scores of students from low income backgrounds in higher vocational colleges and non-poor students, while the subjective support and utilization of support scores were significantly lower than those of non-poor students. In essence, successful social support should not only be one-dimensional support from the subject to the object, but should be a process of two-sided interaction, or a process of “mutual construction” between supporters and those supported. According to the research conclusions, this paper suggests how to improve the degree of mental health of college students by way of forming a comprehensive educational environment including campus culture construction, ideological and moral education, and economic assistance system.